Morphogenetic fields within the dentition - Townsend Grant C.; Brown Tasman (Australasian Orthodontic Journal, 1981)
The concept of genetic control of tooth size and shape by specific morphogenetic fields that control tooth formation originated from studies of the mammalian dentition and later, from the observation that within the human dentition certain key teeth within a class were more stable in size and morphology. More recently, analyses of tooth size from different populations have supported the general ideas inherent in this field theory, however multivariate analyses of tooth size relationships suggest that this genetic control may be more complex than previously envisaged.